Pulmonary Hemorrhage following Edge-to-Edge Mitral Valve Repair - Mirna B. Ayache; Myttle A. Mayuga; Chantal ElAmm; Guilherme Attizzani; Jordan Kazakov (Case Reports in Cardiology)
Mitral valve repair with the MitraClip device has emerged as an effective treatment option for patients with severe mitral regurgitation and contraindications for surgical interventions. While the procedure is not known to cause pulmonary complications, we describe two cases of pulmonary hemorrhage following percutaneous mitral valve repair. The patients did well with supportive care and reinitiation of anticlotting agents was well tolerated after resolution of bleeding.